Carvão ativado de endocarpo de Coco da Baía produzido em forno micro-ondas - Bezerra, Alexandre Freire (2012)
Activated carbon, AC, is a pure state carbon with large porosity, which adsorbs molecules or ions from a fluid medium. In general, it is obtained from the controlled burning of agricultural or industrial by-products. When produced in conventional furnaces, the operating temperatures may rise up to 900°C, resulting in yields inferior to 20 %. The low yield is a consequence of the precursor's large thermal degradation caused by the heat wave front which moves slowly from the surface to its core. Therefore, there is a significant formation of meso and macropores, which lead to a final value of density, ρ, below of 0.5 g.cm-3. On the other hand, thermal degradation caused by microwaves is less aggressive. The heating process occurs from the core of the precursor to its exterior. As a consequence the activated carbons are denser, have a more selective microporosity, and are more suitable to gas storage. This paper reports the preparation and the results of the qualitative analysis of physically and chemically activated carbons, from coconut shell, using an adapted microwave oven. This adapted microwave allows the settling down of temperature programs' ramp and heating rates. The BET surface area of activated carbons prepared in the microwave oven surpassed 1200 m2.g-1, the apparent density situated at around 0.5 g.cm-3, and the yields remained above 40 %. Comparisons between the electricity consumption of the electrical conventional kiln and of the micro-wave oven in producing a certain quantity of an activated carbon with a BET surface area over 800 m2/g, showed that the use of the microwave oven had allowed, each time, a reduction of about 3,2 kW.h, which represents an average of electricity saving of 85.5 %.